Issues Regarding the Nomenclature of D3 Pharmacist in KEPMENDIKTISAINTEKS Number 337/M/KEP/2025: Problematik Nomeklatur D3 Apoteker dalam KEPMENDIKTISAINTEKS Nomor 337/M/KEP/2025 - Syaripah Ulandari; Made Laksmi Meiliana; Dwi Ismayati (Universitas Muhammadiyah Sidoarjo, 2026)
The issuance of Decree No. 337/M/KEP/2025 concerning Higher Education Providers for Medical and Health Personnel Conducting Competency Tests has sparked controversy due to the use of the nomenclature